Miastenia gravis no Ceará, Brasil : aspectos clínicos e epidemiológicos - Aguiar, Aline de Almeida Xavier (2010)
A retrospective chart review of patients diagnosed as having myasthenia gravis, followed in Hospital Universitário Walter Cantídio, Hospital Geral de Fortaleza and by neurologists in Ceará, Brazil, from October 1981 to June 2009 was performed. Clinical and epidemiologic aspects were evaluated. In this work, 122 patients were studied, of whom 85 (69.7%) were females and 37 (30.3%) were males. The disease duration ranged from five months to 50 years (8.9 ± 8.1 years). Age at the first symptoms varied from 0 to 74 years (31.9 ± 14.4 years). The main first symptoms and signs were ptosis, diplopia and member weakness. Generalized myasthenia was the most common clinical presentation, but 5.1% (n=6) persisted as ocular myasthenia. Thymectomy was performed in 42.6% (n=52) of myasthenic patients. A thymoma was present in 10 patients. Serum acetylcholine receptor (AChR) antibodies were present in 80% (n=20) of specimens tested.